MODEL PENDIDIKAN KELUARGA DALAM AL-QUR’AN (ANALISIS TEMATIK AYAT-AYAT AL-QUR’AN TENTANG PENDIDIKAN KELUARGA) - Agusman Agus; Muhammad Hanif; Madeni (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2025)
This study aims to answer the main question: how is the model of family education in the perspective of the Qur’an, and what pillars and methods form its foundation? This research employs a library research method with a thematic tafsir (maudhu’i) approach, examining Qur’anic verses related to family education and analyzing them through both classical and contemporary tafsir literature. The findings reveal that the Qur’anic model of family education consists of four main pillars: (1) aqidah education, which instills monotheism from an early age; (2) worship education, which fosters obedience to the Sharia; (3) moral education, which cultivates noble character; and (4) social education, which develops responsibility toward oneself, family, and society. The methods recommended by the Qur’an include role modeling, wise dialogue, habituation, supervision, and supplication. The impact of this study is expected to contribute to the development of Islamic family education concepts relevant to contemporary challenges and to serve as a practical reference for parents and educators in nurturing a Qur’anic-character generation.